Strategic use of male alternative reproductive tactics in cooperatively breeding banded mongoose groups - Hazel Nichols (Royal Society Open Science, 2025)
Alternative reproductive tactics (ARTs) allow less competitive individuals to reproduce by avoiding direct fights through sneaky strategies. Within cooperatively breeding groups ARTs are rarely reported, potentially owing to observational difficulties or reproductive suppression by group members. In societies where mating opportunities cannot be monopolized by one male, young males could use sneaky tactics as an intermediate ‘stepping-stone’ tactic to gain limited reproductive success while growing in resource-holding potential (RHP). Using decades of pedigree, weight, group demography and behavioural data, we investigated the use of sneaky ‘sneaker’ ARTs in wild male banded mongooses. In this species, groups typically contain more adult males than breeding females, leading to intense male–male competition. Instead of as a stepping-stone, sneaking tactics were typically used by males who had been displaced from mate-guarding status by stronger rivals. Additionally, sneakers had lower siring success compared with mate guards, despite similar weight loss costs, which may explain why males typically avoided reproductive activity entirely rather than sneaking. However, young sneakers gain access to older, higher fecundity females in the group and sneaking may even facilitate inbreeding avoidance. Overall, ARTs in stable social groups can predictively emerge from changes in relative RHP and social status over the lifetime.